Comparative Analisys of Cataract Phakoemulsification, Complicated with the Zonular Weakness - A. N. Kulikov; S. V. Churashov; E. V. Danilenko; D. V. Shamrey; V. S. Kondratov (Oftalʹmologiâ)
Purpose: To assess the iridocrystalline complex status in patients with cataract, complicated by zonular weakness, before and after surgical treatment. Patients and Methods. The study enrolled 28 patients (29 eyes) with cataract, complicated by zonular weakness (8 women, 20 men, 74.13 ± 8.48 years old). All patients undergone phacoemulsification with IOL implantation and a capsular tension ring (CTR) if it was necessary. In each case optical biometry, ultrasound biomicroscopy and applanation tonometry were provided. After 1, 3 and 6 months postoperatively refractometry, visual acuity measurement, optical biometry, ultrasound biomicroscopy and OCT of the anterior segment were carried out. Results. Patients were divided into 2 groups. In I group (17 eyes) standard phacoemulsification was provided.  In II group (11 eyes) it was necessary to implant CTR. 1 patient was excluded due to the extracapsular cataract extraction. Preoperatively angle of the crystalline lens tilt (3.62 ± 0.34° and 1.78 ± 0.27°, p = 0,00) and IOP were higher in group II. 6 months postoperatively UCVA was significantly higher in group II (0.59 ± 0.09 and 0.39 ± 0.21, p = 0.09), upright angle of IOL tilt (0.28 ± 0.35° and 1.40 ± 1.46°, p = 0.10), total zonnular length (14.28 ± 1.00 and 18.93 ± 0.86 mm, p = 0.00) and the value of IOL decentration (0.80 ± 0.17 and 0.20 ± 0.22 mm, p = 0.04) were significantly less in group II. Conclusion. The angle of crystalline lens tilt according to ultrasound biomicroscopy could be considered as an important diagnostic criterion for the CTR implantation necessity during phacoemulsification. CTR implantation provided decrease of IOL tilt and decentration due to a more regular distribution of zonular tension that increases the UCVA postoperatively in complicated cases. OCT of the anterior segment of the eye and ultrasound biomicroscopy application after phacoemulsification gives a great capacity in IOL-capsular complex visualization and measurement.